The kids' book of weather forecasting : build a weather station, "read" the sky & make predictions! - Breen, Mark, 1960- (Williamson Pub., 2008)
A hands-on introduction to the science of meteorology, explaining how to make equipment to measure rainfall, wind direction, and humidity, record measurements and observations in a weather log, make weather predictions, and perform other related activities.